Psychological challenges affecting HIV and AIDS counselors, possible models and solutions: a Zimbabwean perspective - Mbetu-Nzvenga, Jane; Gudyanga, Ephias; Gudyanga, Anna (Canadian Center of Science and Education, 2016)
This paper sought to find out the psychological challenges affecting counselors during HIV and AIDS counseling sessions. The background information focused on what HIV and AIDS counseling is and how it affects counselors and individuals who are HIV positive. Qualitative and quantitative research designs were employed. We randomly sampled ten participants out of a population of thirty (33.3%), eight females and two male nurses/counselors and five female clients who were HIV positive and were living positively. These five had gone through HIV and AIDS counseling. The main data collecting instruments were questionnaires, unstructured interviews and focus grouping. The five clients constituted a focus group. Responses from focus group discussions were presented in a thematic way. It was found out that counselors work under pressure. They face emotional burnout and they are stressed up. They need psychological support from the authorities and colleagues. It was concluded that the Ministry of Health is encouraged to facilitate more workshops and send health workers for further training so as to make them keep abreast with modern trends in HIV counseling and to increase counseling skills as well as to make them feel more competent in their profession.